2019
DOI: 10.1002/mabi.201900096
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Hydrogels for Human Pluripotent Stem Cell–Derived Neural Cells: Hyaluronan‐Polyvinyl Alcohol‐Collagen‐Based Interpenetrating Polymer Network Provides an Improved Hydrogel Scaffold

Abstract: There is a clear need for novel in vitro models, especially for neuronal applications. Development of in vitro models is a multiparameter task consisting of cell‐, biomaterial‐, and environment‐related parameters. Here, three different human origin neuronal cell sources are studied and cultured in various hydrogel 3D scaffolds. For the efficient evaluation of complex results, an indexing method for data is developed and used in principal component analysis (PCA). It is found that no single hydrogel is superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Principal component analysis (PCA) was used as previously described 87 to segregate MEA results from different experiments. The data were derived from two differentiations of hESC line 08/023 (named hPSC 1 and 2) and one differentiation of hiPSC line 10212.EURCCs (named hPSC 3).…”
Section: Methodsmentioning
confidence: 99%
“…Principal component analysis (PCA) was used as previously described 87 to segregate MEA results from different experiments. The data were derived from two differentiations of hESC line 08/023 (named hPSC 1 and 2) and one differentiation of hiPSC line 10212.EURCCs (named hPSC 3).…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant LN-521 has been widely used for stem cell expansion and the generation of neural progenitor cells for disease models and stem cell therapies. [15,48,49] We cross-linked the LN-521 presenting hydrogels by bioorthogonal copper-free click chemistry, which enabled tuning of material properties and creation of biologically relevant microenvironments evidenced by supported encapsulation and culture of both human neuroblastoma cells (SH-SY5Y) and human induced pluripotent stem cell (hiPSC)-derived long-term neuroepithelial stem cells (lt-NES). Furthermore, the hydrogels' favorable and tunable rheological properties provided a protective effect on the lt-NES during syringe extrusion in an in vitro model for cell injection therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion of neurons varies from that of the fibroblasts. The results showed that the synthesized hydrogel acts as a proper scaffold for neuronal cells [115]. Many humans suffer from blindness as a result of corneal diseases.…”
Section: Medical Applicationsmentioning
confidence: 92%